Кібербезпека в проявах ризиків у період пандемії: стан та генеза - Василенко, М. Д.; Василенко, Микола Дмитрович; Новіков, В. П.; Рачук, В. О.; Рачук, Валерій Олександрович; Слатвінська, Валерія Миколаївна; Слатвінська, В. М. (My University, 2020)
Стаття покликана стимулювати інтерес до проявів ризиків у кібербезпеці в умовах COVID-19 (коронавірусу). Зокрема, проаналізовано та надано оцінку проявам кіберризиків у контексті кібербезпеки як нової проблеми, пов’язаної з появою COVID-19, а також з’ясовано її стан та генезу. Запропоновано вирішити проблему управління різними видами ризиків шляхом інституційного розуміння забезпечення юридичного підґрунтя та багатофакторного проєктування або прогнозування, а також запропоновано основний метод посилення захисту – технічний, що використовує, перш за все, алгоритмічні методи, а в окремих випадках – можливість використання сил «Червоної команди» захисної структури. Показано, що в умовах принципово-го збільшення телеконференцій (у період пандемії) суттєво збільшується кількість кіберризиків. Зазначено основні заходи безпеки, потрібні для захисту інформаційно-комунікативної інфраструктури в умовах дії пандемії по COVID-19 (коронавірусу). Авторами доведено, що, оскільки ризики все більше стають послідовними та взаємопов’язаними процесами як невід’ємні складники системи управління, то в цьому випадку більш доречними стають періодичні перевірки офісних приміщень на виявлення використання технічних засобів скритого зняття інформації та періодичне проведення онлайн семінарів зі співробітниками з питань безпеки.

The coronavirus pandemic has created an unprecedented global emergency related to risks, in-cluding cyber-risks, which threaten cybersecurity at both local and global levels. An analysis of the information carried out by the US and EU special institutions confirms that with the appearance of COVID-19 (coronavirus) as a result of a pandemic serious risky economic and political problems are expected with a high percentage of probability. Additional problems are created by the unprecedented transition to online work, when continuous activity during a pandemic occurs mainly using remote operations. Definitions of specific risks are contained in many standards of various sectors of the economy and equipment. However, there is an international standard ISO 31000, which is used for general risk assessment. To implement the risk management process in the current conditions in cybersecurity, it must be integrated with the components of risk management in particular and in general, including the exchange of information and consulting; establishing the context (environment); general risk assess-ment (its identification, analysis and evaluation); processing and summarizing the results of the se-lected type of risk; monitoring and critical analysis, as well as dealing with unforeseen threats. It is shown that in the context of a fundamental increase in teleconferences (during the pandem-ic), the number of cyber risks significantly increases. It is noted that risks are consistent interrelated procedures that are included in the management process and require a more planned systematic ap-proach, given that risk assessment involves studying the state, situation (scenarios) with existing signs of danger, uncertainty and/or randomness. An effective method of its implementation is to provide a legal basis and multi-factor design or forecasting. However, in the first part, the legislative decision almost always comes late. Previously, at the stage of technical risk assessment, a risk management strategy is formed, and since it is impossible to completely avoid risks in most cases, it is important to solve the issue of admissibility (acceptability, justification) of risk, which requires further research and justification. Risk assessment used in technical systems is considered as a process of identifying infor-mation resources of the system and threats to these resources, as well as possible losses, based on an assessment of the frequency of events and the amount of damage. Risk analysis is revealed as the process of identifying risks, determining their magnitude, and identifying areas that require protection. Consequently, the COVID-19 pandemic has created and continues to create social and tech-nical problems that are expressed in the emergence of new risks, new cyber risks. Risks become even more consistent and interconnected processes, inherently entering the management system. In this case it becomes more appropriate to make periodical checks of key premises to identify the use of technical means of hidden information retrieval and periodically conduct online seminars with securi-ty officers.
Кібербезпека в проявах ризиків у період пандемії: стан та генеза / М. Д. Василенко, В. П. Новіков, В. О. Рачук, В. М. Слатвінська // Вісник Черкаського державного технологічного університету, 2020. - Вип. 3. - С. 30-39. DOI: 10.24025/2306-4412.3.2020.214774
Keywords: кібербезпека; ризик; оцінювання ризику; невизначеність; пандемія; COVID-19; cybersecurity; risk; risk assessment; uncertainty; pandemic; COVID-19; Research Subject Categories::TECHNOLOGY; Research Subject Categories::MEDICINE